Expert consensus recommendations on the use of randomized clinical trials for drug approval in psychiatry: comparing trial designs - Von Mücke Similon, Miriam; Paasche, Cecilia; Krol, Fas; Lerer, Bernard; Goodwin, Guy M.; Berk, Michael; Meyer-Lindenberg, Andreas; Ketter, Terence A.; Yatham, Lakshmi N.; Goldberg, Joseph F.; Malhi, Gin S.; El-Mallakh, Rif; et al. (European neuropsychopharmacology, 2022)
The use of randomized clinical trials, in particular placebo-controlled trials, for drug approval, is the subject of long-standing debate in the scientific community and beyond. This study offers consensus recommendations from clinical and academic experts to guide the selection of clinical trial design in psychiatry. Forty-one highly cited clinical psychiatrists and/or researchers participated in a Delphi survey. Consensus statements were developed based on the findings of a published, peer-reviewed systematic review. Participants evaluated statements in two survey rounds, following the Delphi method. The expert panel achieved consensus on 7 of 21 recommendations regarding the use of randomized clinical trials. The endorsed recommendations were: (i) Results from placebo-controlled trials are the most reliable and (ii) are necessary despite the growing placebo-effect; (iii) it is ethical to enroll patients in placebo-arms when established treatment is available, if there is no evidence of increased health risk; (iv) There is a need to approve new drugs with the same efficacy as existing treatments, but with different side-effect profiles; (v) Non-inferiority trials incur an increased risk of approving ineffective medications; (vi) The risk of approving an ineffective drug justifies trial designs that incur higher costs, and (vii) superiority trials incur the risk of rejecting potentially efficacious treatments. The endorsed recommendations inform the choice of trial-design appropriate for approval of psychopharmacological drugs. The recommendations strongly support the use of randomized clinical trials in general, and the use of placebo-controlled trials in particular.